Tracing the immigrant narrative in the novel Babel through mapping identity and belonging - Prafitri, Wilma; Nasir, Muhammad Alim Akbar; Triyoga, Anwar Ibrahim (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This research examines the immigrant experience in R.F. Kuang’s Babel: An Arcane History of the Oxford Translators’Revolution (2022), emphasizing the interplay of language, power, and identity within the colonial context of 19th-century Oxford. This project employs a synthesis of postcolonial literary theory and literary cartography to delineate the emotional and spatial trajectories of immigrant characters, with a focus on Robin Swift, a Chinese orphan reared in England. The analysis demonstrates that translation serves as both an instrument of imperial control and a locus of resistance, situating immigrant scholars as both vital and marginalized within the empire. This research employs meticulous textual analysis to reveal patterns of assimilation, alienation, and rebellion, demonstrating how Kuang’s story critiques colonial processes and reasserts linguistic agency. This multidisciplinary approach provides a unique contribution to Babel study by depicting immigrant identity as a dynamic negotiation of cultural memory, displacement, and resistance.